The Motif of Worship, Prayer, and Prophecy in Luke 1:5–25 as a Bridge between the Old Testament and the Gospel of Luke - Aryeh, Daniel Nii Aboagye (Scriptura, 2024)
This article provides an exegetical contribution to the proposition by David E. Garland that the Old Testament period of the promise found fulfilment in the New Testament. The specific contribution of this study is the elements/traces of a bridge between the Old Testament and the annunciation/nativity narrative of Luke 1:5-25. The Gospel of Luke is characterised by people worshipping, praying, and fulfilling prophecy, as evidenced in the first two chapters of the book. There have been studies on the nativity narrative of the Gospel of Luke which usually took a historical comparative approach between the birth narrative of Jesus and that of John, and investigations into the uniqueness of the story to Luke. It leaves out the thematic discussion of some ethoses of the annunciation narrative that seeks to provide an unflinching link to the Old Testament. This article examines worship, prayer, and prophecy in the annunciation and nativity narrative in Luke 1:5-25 to draw possible relationships to the Old Testament. The diachronic narrative-semantic method is used for the study. The findings are that the narrative alludes to Old Testament stories of worship, prayer, and fulfilment of prophecy and suggests a link or bridge between the Old and New Testaments.